Assessment of functional tests on determining resistance of respiratory tract in patients with bronchial asthma, COPD and their combination. - K. V. Nazarenko; S. G. Opimakh; M. O. Polianskaja (Medičnì Perspektivi)
The mechanical properties of the respiratory tract (including airway resistance) is an important indicator of pulmonary function, and definition of resistance is used to diagnose and monitor obstructive lung diseases. This study was performed in order to evaluate and compare functional results of tests to determine the resistance of the airways in patients with asthma, chronic obstructive pulmonary disease and their combination. The study involved 191 patients: with asthma (n=34), with COPD (n=17) and their combination (n=140). Patients underwent bodyplethysmography and impulse oscillometry. A statistically significant correlation of medium strength between parameters of the total resistance, determined with the help of bodyplethysmography and impulse oscillometry, r=0.57, p<0.001. According to ROC-analysis, the best point of distribution of normal and pathological parameters of impulse oscillometry (R5Hz) as a diagnosis of increased respiratory resistance is 130% and higher from the proper values. The area under the ROC curve is 0.807. When interpreting the results of impulse oscillometry in patients with asthma, COPD and their combination, R5Hz level equal to or exceeding 130% of the proper values is proposed to be regarded as a sign of an increased respiratory resistance with sensitivity of technique – 64.0%, specificity – 87.5% and prognostic value of the positive result - 98.2%.